Precursor film formation on catalyst–electrolyte–gas boundaries during CO2 electroreduction with gas diffusion electrodes - H Yildirim Erbil (Catalysis science & technology, 2022)
The location of the CO2 electroreduction reaction on catalytic layers (CLs) is a subject of debate when gas diffusion electrodes (GDEs) are used. This perspective article discusses the possible formation of narrow, thin, and long layers of precursor films of aqueous catholytes, which spread very close to the triple-phase boundaries (TPBs) on superaerophilic CL composite layers containing hydrophobic polymers and hydrophilic catalysts. TPB is the meeting location of the electrolyte, gas, and catalyst phases, where the dissolved CO2 molecules in the precursor films in high concentrations are supplied from the nearby CO2 gas phase, which passes through the GDE via the carbon fiber and microporous layers. Dissolved CO2 in the precursor film is reduced on the catalyst surface at TPB without depletion. Thus, the conditions for the formation and persistence of long TPB on the composite catalysis layer play an important role in the high efficiency of CO2 electroreduction. The publications reporting high performances of CO2 electroreduction, which were attributed to the TPB formation when using GDE-type (and also some H-type) systems, are reviewed in this study with some advice for future research.